Pengaruh Privasi, Kepercayaan, Kemudahan, Persepsi Manfaat dan Persepsi Risiko Terhadap Minat Bertransaksi Secara Online (Studi Kasus Pada Mahasiswa Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta) - Setyorini, Eka; , Dra. Nursiam, M.H., Ak., CA (2017)
The study aimed to determine the effect of privacy, trust, ease, perceived usefulness and perceived risk to the nterest in online transaction in accounting study program students of the Faculty of Economics and Business at Muhammadiyah University of Surakarta force 2013-2016.This research uses quantitative method with primary data that ectingquestionnaire. In the study the samples were 94 students study program accounting Faculty Economic and Business Muhammadiyah University of Surakarta force 2013-2016. The sampling tehnique used is convenience sampling. Data analysis method used in this study was multiple linear regression analysis.. The data obtained are then analyzed using SPSS versi 17. The results showed that influence of privacy, trust and ease has effect on the interest in online transaction, while perceived usefulness and perceived risk has not effect on the interest in online transaction